Ozone and water vapor variability in the polar middle atmosphere observed with ground-based microwave radiometers - G. Shi; W. Krochin; E. Sauvageat; G. Stober (Atmospheric Chemistry and Physics, 2023)
Leveraging continuous ozone and water vapor measurements with the two ground-based radiometers GROMOS-C and MIAWARA-C at Ny-Ålesund, Svalbard (79 ∘ N, 12 ∘ E) that started in September 2015 and combining MERRA-2 and Aura-MLS datasets, we analyze the interannual behavior and differences in ozone and water vapor and compile climatologies of both trace gases describing the annual variation of ozone and water vapor at polar latitudes. A climatological comparison of the measurements from our ground-based radiometers with reanalysis and satellite data was performed. Overall differences between GROMOS-C and Aura-MLS ozone volume mixing ratio (VMR) climatology are mainly within ± 7 % throughout the middle and upper stratosphere and exceed 10 % in the lower mesosphere (1–0.1 hPa) in March and October. For the water vapor climatology, the average 5 % agreement is between MIAWARA-C and Aura-MLS water vapor VMR values throughout the stratosphere and mesosphere (100–0.01 hPa). The comparison to MERRA-2 yields an agreement that reveals discrepancies larger than 50 % above 0.2 hPa depending on the implemented radiative transfer schemes and other model physics. Furthermore, we perform a conjugate latitude comparison by defining a virtual station in the Southern Hemisphere at the geographic coordinate (79 ∘ S, 12 ∘ E) to investigate interhemispheric differences in the atmospheric compositions. Both trace gases show much more pronounced interannual and seasonal variability in the Northern Hemisphere than in the Southern Hemisphere. We estimate the effective water vapor transport vertical velocities corresponding to upwelling and downwelling periods driven by the residual circulation. In the Northern Hemisphere, the water vapor ascent rate (5 May to 20 June in 2015, 2016, 2017, 2018, and 2021 and 15 April to 31 May in 2019 and 2020) is 3.4 ± 1.9 mm s −1 from MIAWARA-C and 4.6 ± 1.8 mm s −1 from Aura-MLS, and the descent rate (15 September to 31 October in 2015–2021) is 5.0 ± 1.1 mm s −1 from MIAWARA-C and 5.4 ± 1.5 mm s −1 from ...